Does Intracerebral Hemorrhage Mimic Benign Dizziness Presentations? A Population Based Study - Kerber, Kevin A. (2011)
OBJECTIVE: A principal reason to order a head computerized tomography (CT) scan for dizziness patients is to exclude stroke. Since CT imaging is substantially limited in assessing for any acute lesions other than hemorrhage, the most important stroke syndrome adequately evaluated by CT is intracerebral hemorrhage (ICH). We used a population-based stroke database to assess the frequency with which ICH might mimic a benign dizziness presentation. METHODS: The Brain Attack Surveillance in Corpus Christi (BASIC) project was used to identify cases of ICH from January 1, 2000, to December 26, 2007. The hospital records of ICH cases with a National Institutes of Health Stroke Scale (NIHSS) of < 2 were abstracted for more detailed information. Cases were classified as benign dizziness presentations when isolated dizziness and a normal general neurological examination were documented. RESULTS: Of 595 ICH cases, only 2.2% (13 of 595) had dizziness as the primary presenting symptom and an NIHSS < 2. No case mimicked a benign dizziness presentation. Only one case had isolated dizziness symptoms but this patient had dysmetria documented on the exam. All other cases had either focal or global neurological symptoms or exam abnormalities. CONCLUSIONS: This study provides further support for the notion that ICH is highly unlikely to mimic a benign dizziness presentation. Coupled with the limitations of CT to show acute ischemia in the posterior fossa, these results suggest that screening for ICH may not be necessary in benign appearing dizziness presentations, though more research is needed.